PEMANFAATAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMPN 4 BINAMU JENEPONTO - Hanafy, Muhammad Sain; ., Reski (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to answer the problem formulation, namely: 1) For the utilization of Islamic Religious Education teaching materials based on the learning stick type of talking stick type at SMPN 4 Binamu Jeneponto, 2) To find out the learning outcomes of Islamic Religious Education students who do not utilize teaching materials Islamic Religious Education based on the learning stick type of talking stick type at Binamu Jeneponto SMPN 4, 3) To find out the learning outcomes of Islamic Religious Education students who utilize teaching materials Islamic Education based on the talking stick type cooperative learning model at SMPN 4 Binamu Jeneponto, and 4) To find out the difference in the improvement of student learning outcomes after utilizing Islamic Religious Education teaching materials based on the type of cooperative learning model talking stick in SMPN 4 Binamu Jeneponto.The results showed that the utilization of Islamic Religious Education teaching materials based on the cooperative learning model of talking stick type at SMPN 4 Binamu Jeneponto by dividing students into several groups, then educators distributing teaching materials to students. Furthermore, students are given a few minutes to study teaching materials in Islamic Education through modules. Each group reads, discusses, and looks for problems on each topic in the material. Next the educator takes the stick and gives it to one of the groups, after that the educator gives a question and the group member who holds the stick must answer it, and so on until most of the students get a part to answer each question from the educator. Furthermore, students can help answer questions if the group members cannot answer those questions that take place during the teaching-learning process until the evaluation. The average learning outcomes of students in the pretest control class is 61.25 and posttest 74.50. While the average learning outcomes of experimental class students are pretest 63.25 and posttest 85.75. While the t-test results of the two groups are at a significance of 0,000 less than 0.05 which means that H0 is rejected and H1 is accepted.The implication of this research is the use of teaching materials for Islamic Religious Education based on the Cooperative Learning Model talking stick type suitable to be applied in junior high schools, especially at SMPN 4 Binamu Jeneponto. However, the use of the talking stick Cooperative Learning Model should be implemented with full supervision from the teacher as a facilitator so that the course of the class will be more effective.